Movement of Moths Through Riparian Reserves Within Oil Palm Plantations - Gray, Ross E. J.; Slade, Eleanor M.; Chung, Arthur Y. C.; Lewis, Owen T. (Frontiers in Forests and Global Change, 2019)
Tropical forests are becoming increasingly fragmented through conversion to agriculture, with negative consequences for biodiversity. Movement of individuals among the remaining fragments is critical to allow populations of forest-dependent taxa to persist. In SE Asia, conversion of forests to oil palm plantations is a particular threat. Many oil palm dominated landscapes retain forested riparian reserves along streams and rivers, but the extent to which these riparian reserves are used for movement, relative to the oil palm matrix, is poorly understood. We used mark-release-recapture methods to investigate the movement of five moth taxa in riparian reserves connected to a continuous forest area within oil palm matrix in Sabah, Malaysian Borneo. Moths were recaptured on average 68m from the release point, and the mean time to recapture was between 2 and 3 days. Moths showed a significant tendency to move within forested riparian reserves than into adjacent oil palm. When moving within riparian reserves moths also showed a tendency to orient their movement away from the continuous forest into the riparian reserve rather than towards continuous forest or into oil palm. Overall, our results show a role for riparian reserves as movement corridors through oil palm plantations for some invertebrate species, strengthening the case for their retention and re-establishment.